Implementasi Peraturan Daerah Kota Semarang Nomor 5 Tahun 2010 tentang Pengendalian Penyakit Demam Berdarah Dengue di Kecamatan Tembalang Kota Semarang - Galuh Rakasiwi; Aloysius Rengga (Journal of Public Policy and Management Review, 2017)
Management of Dengue Hemorrhagic Fever (DHF) is a prevention and mitigation activities to break the chain of infection dengue disease in a way to combat mosquitoes and mosquito larvae of Aedes aegypti and Aedesalbopictus. Dengue is one of endemic disease in Semarang City. District Tembalang, which is one of district in Semarang City, has the highest number of patients with dengue fever within the last five years. Seeing this, Semarang City Government published Perda No. 5 tahun 2010 about Dengue Hemorrhagic Fever (DHF) Management. This study is aimed to describe how the implementation of Perda No. 5 tahun 2010 about Management of Dengue Hemorrhagic Fever (DHF) Management in district Tembalang and to identify supporting factors and resisting factors of Implementation Perda No. 5 tahun 2010 about Dengue Hemorrhagic Fever (DHF) Management in District Tembalang. This research is a descriptive study using a qualitative approach. The result shows there are phenomenon that considered not good enough such as accuracy of the policy, accuracy of the implementer, accuracy in targeting, precision and accuracy of the process environment. In this study also found that supporting factors of the regulation implementation is bureaucratic structure, whereas the resisting factors founded in the communication factor, resources and disposition. Recommendations can be given by researcher are to increase the intensity of regulation socialization, community empowerment, strengthen of coordination between the implementers, enhance human resources quantity, cooperate with other implementers such as private implementers in order to support the lack of budget.